A Survey of Sedation Practices for Colonoscopy in Canada - Peter Porostocky; Naoki Chiba; Palma Colacino; Dan Sadowski; Harminder Singh (Canadian Journal of Gastroenterology)
BACKGROUND: There are limited data regarding the use of sedation for colonoscopy and concomitant monitoring practices in different countries.